2006
DOI: 10.1590/s0102-695x2006000300013
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e validação de metodologia para quantificação de alcalóides totais como berberina em fitoterápico contendo Berberis vulgaris L.

Abstract: Unitermos: Robusterina® , fi toterápico, validação, alcalóides, doseamento.ABSTRACT: "Development and validation of a method for the quantifi cation of total alkaloids as berberine in an herbal medicine containing Berberis vulgaris L.". Robusterina ® is a herbal medicine, with effectiveness in the treatment of menstrual cycle disfunctions. Its composition includes Berberis vulgaris L., with sedative and antispasmodic action; Gossypium herbaceum L., with emmenagogue, hemostatic and ocitocic action; Viburnum opu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…A "tintura do algodoeiro" is used as a component in a phytotherapeutic agent (Robuterina ® ), which is used to treat menstrual cycle disorders. This medicine further includes Berberis vulgaris L., and Gossypium herbaceum L. It also acts as an emmenagogue, hemostatic and ocitocic and has anti-inflammatory activity (Oliveira et al, 2006). Preclinical toxicity of a phytotherapeutic preparation containing Gossypium herbaceum (Cotton Plant) was tested by Mello et al (2008), whose results revealed the absence of systemic toxicity at a therapeutic dose.…”
Section: Plants Used In Screening and Their Pharmacological Activitiesmentioning
confidence: 99%
“…A "tintura do algodoeiro" is used as a component in a phytotherapeutic agent (Robuterina ® ), which is used to treat menstrual cycle disorders. This medicine further includes Berberis vulgaris L., and Gossypium herbaceum L. It also acts as an emmenagogue, hemostatic and ocitocic and has anti-inflammatory activity (Oliveira et al, 2006). Preclinical toxicity of a phytotherapeutic preparation containing Gossypium herbaceum (Cotton Plant) was tested by Mello et al (2008), whose results revealed the absence of systemic toxicity at a therapeutic dose.…”
Section: Plants Used In Screening and Their Pharmacological Activitiesmentioning
confidence: 99%
“…All aqueous extracts obtained were subjected to analysis to determine the contents of phenolic compounds (Djeridane et al, 2006), total alkaloids (Oliveira et al, 2006) and antioxidant activity (Kumaran & Karunakaran, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…For each sample, the spectrophotometer reading was performed at 435 nm wavelength. Blank was obtained by mixing nitric acid and thiourea (Oliveira et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the total alkaloid content was determined according to the methodology described by Oliveira et al [20]. For this, two g of plant material was reacted with eight mL of 10% acetic acid, prepared in ethanol, for four h, filtered and precipitated with concentrated ammonium hydroxide.…”
Section: Analysis Of the Alkaloid Contentsmentioning
confidence: 99%